The Standard of Proof for Redressing Wrongful Convictions - A Comparative Study with Case Analyses - Jiahong, He (International Journal of Criminology and Sociology, 2015)
Instances of wrongful conviction have the nature of universality and latency. The determination of wrongful conviction has the nature of ambiguousness and antagonism. The facts behind a case of wrongful conviction are not always black-and-white; sometimes there is a grey zone, meaning that there is no way to determine with accuracy whether the defendant is guilty or not. As a result, the rectification of wrongful conviction becomes very difficult. In the case of Hugejiletu, for example, although the true perpetrator came out in 2005, the wrongful conviction had not been corrected by the court until the end of 2014. Therefore, the standard of proof for redressing wrongful convictions needs to be clarified. Through case analyses of the standard in USA, UK and Germany, we can see that the standard for redressing wrongful convictions are different from the standard for convictions, with the former being generally lower than the latter. We should restate the standard of proof for redressing wrongful convictions in Chinese criminal proceedings, and make distinctions between the standard for starting a retrial, the standard for redressing a wrongful conviction, and the standard for awarding a state compensation.